2015
DOI: 10.5424/sjar/2015133-7308
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication. Embryo yield in llamas synchronized with two different intravaginal progesterone-releasing devices and superovulated with eCG

Abstract: The objectives of this study were to compare the effects of two intravaginal devices (ID) containing the same dose (0.5 g) of progesterone (P 4 ) on subsequent ovarian response, embryo production and circulating P 4 concentration profile in llamas (Lama glama) treated with equine chorionic gonadotropin (eCG) for ovarian superstimulation. Female llamas were randomly assigned (n = 10 llamas per group) to one of the following groups and treated (Day 0) with an ID containing 0.5 g of vegetal P 4 to synchronize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
2
1
Order By: Relevance
“…Besides, Aller et al. () proved in superovulated llamas that all animals were sexually receptive by day 2 after the end of P 4 treatment, although no description of follicular development was reported in this study. Meanwhile, there are no studies characterizing plasma P 4 concentrations and their effects on follicular activity in llamas treated with IVDs containing lower or higher P 4 concentrations than those previously evaluated.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Besides, Aller et al. () proved in superovulated llamas that all animals were sexually receptive by day 2 after the end of P 4 treatment, although no description of follicular development was reported in this study. Meanwhile, there are no studies characterizing plasma P 4 concentrations and their effects on follicular activity in llamas treated with IVDs containing lower or higher P 4 concentrations than those previously evaluated.…”
Section: Introductioncontrasting
confidence: 65%
“…However, after CIDR ® insertion, concentrations sharply decreased until day 3 after insertion, while the device containing 780 mg in the present study maintain concentrations around maximum until device withdrawal. Besides different P 4 contents in the devices, it has been suggested in llamas (Aller et al., ) and cows (van Werven et al., ) that differences in contact surface area between devices result in different P 4 plasma concentrations patterns. It could be speculated that in the present study, differences between devices hormone release may partly be responsible for the observed patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration rapidly decreased until Day 3 of treatment and then decreased slowly, until reaching basal levels. Aller et al (2015) obtained this same pattern of circulating progesterone using two different intravaginal devices containing the same dose (500 mg). Besides, the results of the present study showed that the treatment of 150 mg of Progesterone BioRelease ® LA was more efficient in inhibiting the ovarian follicular dynamics and it was observed follicular growth by Day 7 and 8 and an ovulatory size follicle at the end of the treatment (Day 10).…”
Section: Discussionmentioning
confidence: 63%